2021
DOI: 10.3390/ph14030211
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Induces the Expression and Function of Tryptophan-2-3-Dioxygenase in SK-MEL-28 Melanoma Cells

Abstract: Tryptophan-2,3-dioxygenase (TDO) is one of the key tryptophan-catabolizing enzymes with immunoregulatory properties in cancer. Contrary to expectation, clinical trials showed that inhibitors of the ubiquitously expressed enzyme, indoleamine-2,3-dioxygenase-1 (IDO1), do not provide benefits in melanoma patients. This prompted the hypothesis that TDO may be a more attractive target. Because the promoter of TDO harbors glucocorticoid response elements (GREs), we aimed to assess whether dexamethasone (dex), a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Moreover, pretreatment of parental cells with 680C91 significantly abolished expression of these stemness markers in control unstimulated spheres, suggesting that TDO may regulate those genes in unstimulated cells as well. Our recently published report and this study clearly show that dex upregulates TDO (Cecchi et al, 2021), whose inhibition abrogated melanoma cell spherogenesis and suppressed the up-regulation of stem cell markers.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Moreover, pretreatment of parental cells with 680C91 significantly abolished expression of these stemness markers in control unstimulated spheres, suggesting that TDO may regulate those genes in unstimulated cells as well. Our recently published report and this study clearly show that dex upregulates TDO (Cecchi et al, 2021), whose inhibition abrogated melanoma cell spherogenesis and suppressed the up-regulation of stem cell markers.…”
Section: Discussionsupporting
confidence: 71%
“…We recently showed that TDO is expressed in SK-Mel-28 cells, and that this expression is upregulated by dex with maximal effects achieved at 25 µM ( Cecchi et al, 2021 ). To test whether this expression is restricted to this cell line, we employed a more aggressive melanoma cell line, namely A375 ( Rossi et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations